The Poet and the Transgenerational. Notes on the Ethical Legacy of the Poetic in Osip Mandelstam, Paul Celan, and Durs Grünbein (Configurazioni. Research on contemporary poetry, 2022)
The paper addresses the question of the transgenerational by analysing a selection of writings by Osip Mandel’štam (1891-1938), Paul Celan (1920-1970), and Durs Grünbein (1962). The work suggests that the «unconscious of the text» (André Green) of these poets is permeated by a concern for the dynamics of transmission. In these terms, poetry can be interpreted as a space of survival of an absence, which represents a source of resignification of a possible encounter between distant generations in time and space.
Keywords: Paul Celan; Durs Grünbein; area of the “poetic”; transgenerational; Osip Mandelstam